Development of national qualifications frameworks in Europe - (:unkn) unknown (Publications Office of the European Union, 2012)
This third Cedefop review on the development of national qualifications frameworks (NQFs) in the 27 EU member states, five EU candidate countries and Liechtenstein and Norway shows rapid progress towards establishing and implementing NQFs. By the end of 2011, 12 countries (Belgium (Flanders), the Czech Republic, Denmark, Estonia, Ireland, France, Latvia, Lithuania, Malta, the Netherlands, Portugal and the UK) have linked their national qualifications levels to the European qualifications framework (EQF) levels. These countries consider NQFs as tools that support national reforms and coherent lifelong learning policies. By promoting the use of learning outcomes they address barriers between vocational education and training and higher education. The report pays particular attention to the links between NQFs and validation of non-formal and informal learning, a link which is becoming stronger in in most of the countries reviewed. (BIBB-Doku)
Keywords: S 2.3 Berufsbildungspolitik; I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; G 2.5.3 Anschlussfähigkeit von Bildungsgängen; I 2.2 Europa; EU-Bildungspolitik; Nationaler Qualifikationsrahmen; Europäischer Qualifikationsrahmen; Durchlässigkeit im Bildungssystem; Lebenslanges Lernen; Europäische Union; Kroatien; Mazedonien; Montenegro; Türkei; Island; Liechtenstein; Norwegen